Graphitization resistance determines super hardness of lonsdaleite, nanotwinned and nanopolycrystalline diamond. (July 2018) - Ma, Xiaoliang; Shi, Liping; He, Xiaodong; Li, Long; Cao, Guojian; Hou, Chengyu; Li, Jiacheng; Chang, Li; Yang, Lin; Zhong, Yesheng
Abstract: Recent experiments have reported that nanotwinned and nanopolycrystalline diamond-like materials exhibit unprecedented hardness, enhanced fracture toughness, and improved thermal stability. This extraordinary finding has raised fundamental issues on atomistic hardening mechanisms governing the combined resistance to indentation of the chemical bonds in these nanostructured hardest covalent solids. Indentation-induced transition from diamond, nanopolycrystalline diamond and nanotwinned diamond into graphite at the area of indentation has been experimentally confirmed. Here, using molecular dynamics simulation, we unveil a new graphitization resistance dominated hardening mechanism that hinders graphitization by introducing a large number of twin boundaries (TBs) and grain boundaries (GBs) commonly known in nanostructured diamond, leading to greatly enhanced hardness of an indented diamond lattice. This remarkable nanostructure-generated additional graphitization resistance mechanism offers fundamental insights for understanding and improving the stress response of nanotwinned and nanopolycrystalline diamond under indentation and is verified by comparing the results with those from the experiment. Graphical abstract: Image 1